2022
DOI: 10.1088/1742-6596/2314/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofilms developed from alginate extracted from Padina sp. incorporated with calcium chloride (CaCl2)

Abstract: Seaweed has been used in many industries, whether directly or its extract. Padina sp. is one of the understudied species of brown seaweed. Brown seaweed have alginate embedded in their cell wall which is a type of hydrocolloids and can be used in many industries and applications including development of biofilms. The main objective of this current study is to develop biofilms using alginate extracted from Padina sp. and incorporated with calcium chloride at different concentrations. Prior to that, the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The maximum breaking strength is 26.5 MPa, which is much higher than those reported in the literature (Tables S1). [9][10][11]16,28,31] The breaking strain is 3.6 times of that of the pristine SA film and is comparable to those of the modified sodium alginate film reported previously (Table S2). Moreover, the Young's modulus and the strength at break are 10 MPa and 26.5 MPa, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The maximum breaking strength is 26.5 MPa, which is much higher than those reported in the literature (Tables S1). [9][10][11]16,28,31] The breaking strain is 3.6 times of that of the pristine SA film and is comparable to those of the modified sodium alginate film reported previously (Table S2). Moreover, the Young's modulus and the strength at break are 10 MPa and 26.5 MPa, respectively.…”
Section: Resultssupporting
confidence: 87%
“…The optimal SA to PEG ratio is 4 : 1 at which the mechanical strength of SA/PEG/FeCl 3 reaches the maximum. The maximum breaking strength is 26.5 MPa, which is much higher than those reported in the literature (Tables S1) [9–11,16,28,31] . The breaking strain is 3.6 times of that of the pristine SA film and is comparable to those of the modified sodium alginate film reported previously (Table S2).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…It was concluded that both K. alvarezii-and alginate-based films individually each have their own pros and cons. Hanry et al (2022) and Hanry & Surugau (2020) studies revealed that there was more room for the use of K. alvarezii-and alginate-based bioplastics with the goal of replacing single-use packaging. This study is a follow-up that aims to serve as a baseline reference for following research by comparing each characteristic to assess the effects of combining commercial sodium alginate with K. alvarezii at various ratios to produce seaweedbased bioplastics.…”
Section: 0mentioning
confidence: 99%